ANALISIS SPASIAL TITIK DAN JALUR EVAKUASI DALAM MITIGASI PENGURANGAN RISIKO BENCANA BANJIR DI KECAMATAN MANDONGA KOTA KENDARI - Hasddin Hasddin; Erny Tamburaka (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
This study analyzes the distribution of flood areas and the determination of evacuation sites and routes in Mandonga District, Kendari City. This research uses a quantitative design and a survey. Data were analyzed spatially with ArcView 3.2 application. The results showed that the floods that occurred in Mandonga District, Kendari City during 2015-2018 were 416.23 ha or around 37.45% of the total area of ​​Mandonga District (1,111.47 ha), spread throughout the region (in six villages). There are six (6) points that are suitable as main evacuation points for flood refugees in Mandonga District, 1 point in Labibia Village, 2 points in Wawombalata Village, and 3 points in Mandonga Village. There are 11 path points namely; Jl. Imam Bonjol; Jl. Subsidy; Jl. Sawerigading (Anggilowu); Jl. Sawerigading (Mandonga); Jl. Taridala; Jl. Lasandara; Jl. Made Sabara; Jl. Tax; Jl. Welado; Jl. Supu Yusuf; and Jl. Sidendreng.